International standards and international trade evidence from Caricom economies - Densil Williams (Centro de Investigaciones Comerciales e Iniciativas Académicas, 2012)
This paper analyzed the relationship between international standards and international trade between United States, a developed economy and countries in Caricom, a regional integration movement of small, developing economies in the Caribbean. The empirical literature on the relationship between standards and international trade is very limited. This is especially so for small, developing economies like those in Caricom. To advance this literature, the paper used an augmented gravity model with panel data for 14 Caricom countries for the period 1991-2009 to test the relationship. The estimated model showed that economic size and distance, not international standards, are the most significant factors that determine trade flows between Caricom and the United States. In other words, international standard of quality is treated as a sunk cost in conducting international business/trade.